Production of cross-linked enzyme aggregate-lipase from channel catfish (ictularus punctatus) viscera - Mahmod, Safa Senan; Yusof, Faridah; Jami, Mohammed Saedi (2014)
Cross linked enzyme aggregates technology is one of the latest methods in immobilization of enzymes. This technique provides biocatalysts with higher activity, stability and reusability in industrial applications. In this research, lipase was extracted from the viscera of river channel catfish (Ictularus punctatus) and was immobilized based on cross-liked enzyme aggregate methodology. Glutaraldehyde was used as a cross-linker, acetone as precipitant and bovine serum albumin as an additive to improve the formation of CLEA-lipase. Experimental design was carried out by Response Surface Methodology using central composite design to find the optimum conditions for immobilization which was 50 mM of glutaraldehyde, 60% (v/v) Acetone and 0.11 mM of BSA. Finally, CLEA-lipase’s specific activity was 1.713 U/mg that is 20.43% higher than the free lipase activity.